2018
DOI: 10.3892/ijmm.2018.3907
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated decline in Nrf2 signaling and associated mtDNA damage may be involved in the degeneration of the auditory cortex: Implications for central presbycusis

Abstract: Central presbycusis is the most common sensory disorder in the elderly population, however, the underlying molecular mechanism remains unclear. NF-E2-related factor 2 (Nrf2) is a key transcription factor in the cellular response to oxidative stress, however, the role of Nrf2 in central presbycusis remains to be elucidated. The aim of the present study was to investigate the pathogenesis of central presbycusis using a mimetic aging model induced by D-galactose (D-gal) in vivo and in vitro. The degeneration of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…A role has also been described for NRF2 in maintaining mitochondrial integrity and regulating mitochondrial biogenesis. It has been reported that NRF2 activation protects mitochondria by opening the mitochondrial permeability transition pore (Lee et al, 2000;Greco and Fiskum, 2010;Greco et al, 2011) and that declining NRF2 signaling is associated with increased damage to mitochondrial DNA (mtDNA; Li et al, 2018). In addition, NRF2 activation modulates the expression of ATP synthase subunit a and NDUFA4, two components of the electron transport chain (Abdullah et al, 2012;Agyeman et al, 2012), and mice in which NRF2 has been deleted have lower mtDNA globally than wild-type (WT) mice (Zhang et al, 2013).…”
Section: Mitochondrial Role Of Nrf2mentioning
confidence: 99%
“…A role has also been described for NRF2 in maintaining mitochondrial integrity and regulating mitochondrial biogenesis. It has been reported that NRF2 activation protects mitochondria by opening the mitochondrial permeability transition pore (Lee et al, 2000;Greco and Fiskum, 2010;Greco et al, 2011) and that declining NRF2 signaling is associated with increased damage to mitochondrial DNA (mtDNA; Li et al, 2018). In addition, NRF2 activation modulates the expression of ATP synthase subunit a and NDUFA4, two components of the electron transport chain (Abdullah et al, 2012;Agyeman et al, 2012), and mice in which NRF2 has been deleted have lower mtDNA globally than wild-type (WT) mice (Zhang et al, 2013).…”
Section: Mitochondrial Role Of Nrf2mentioning
confidence: 99%
“…They also speculated that “Nrf2 might act as a molecular link between brain aging and AD” (Branca et al, 2017). Numerous laboratories supported this hypothesis showing that Nrf2 activity decreased with aging (Suh et al, 2004; Zhang et al, 2015; Li et al, 2018). Moreover, Nrf2 activity is strictly related to tau pathology, enhancing the link between Nrf2 and AD (Lastres-Becker et al, 2014).…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, changes in ROS elimination caused by aging are likely to vary depending on the tissues and contexts. Antioxidant defense activities were reported to decrease in cochlea and brain during aging 68,69 ; however, other reports showed that antioxidant defense activities in the muscle and brain remained unchanged or increased 65,[70][71][72] . In this study, we found that NRF2 pathway activity was not changed in the cochleae for as long as 12 months.…”
Section: Discussionmentioning
confidence: 99%